Comparison of Efficacy of Azithromycin with Ciprofloxacin in the Treatment of Uncomplicated Enteric Fever in Children - Akram, Maimoona; Ain, Qurrat ul; Tariq, Ayesha; Javed, Samra; Nayab, Kiran; Fatima, Sampana (Journal of Rawalpindi Medical College, 2025)
Objective: To compare the effectiveness of azithromycin to ciprofloxacin in the management of uncomplicated enteric fever in children between 6-12 years of age in the paediatrics department of Pakistan Atomic Energy Commission (PAEC) General Hospital. Methods: It was a randomized control trial study, conducted at the Department of Pediatrics, PAEC General Hospital, Islamabad from 30-01-21 to 30-07-22. Data from 196 children with signs and symptoms of uncomplicated enteric fever was collected after obtaining verbal consent from their parents. Demographic information of the patients along with a short medical history were noted in pre-designed forms. Results: Mean age, treatment time, body weight and defervescence time in the azithromycin group were 9.21±2.24 years, 5.87±1.78 days, 28.3±4.54 kg and 49.8±10.21 hours, respectively. Similarly, age, treatment duration, body weight and defervescence time in the ciprofloxacin group were 9.48±2.41 years, 6.41±1.14 days, 26.9±4.89 kg and 53.7±12.25 hours, respectively. The observed efficacy was 92 (93.9%) and 74 (75.5%) in the azithromycin and ciprofloxacin groups, respectively. Conclusion: Azithromycin is an efficient outdoor patient treatment choice for children with uncomplicated typhoid fever and needs to be widely utilized in high-risk fluoroquinolone-resistant countries. Keywords: Multi-Drug Resistance; Salmonella Typhi; Azithromycin; Ciprofloxacin.